The Influence of Financial Literacy, Family Environment, and Lifestyle on Financial Management of Economic Education Students - SANASYA, Yahdinil Husna; FITRAYATI, Dhiah (Journal of Governance, Taxation and Auditing, 2025)
This study aims to analyze the influence of financial literacy, family environment, and lifestyle on students' financial management. This study used a quantitative approach with a causal associative design. The population in this study was all active students of the Economics Education Study Program, Surabaya State University, graduating in 2021–2023, totaling 377 people. A sample of 194 students was obtained using a proportionate stratified random sampling technique based on year of enrollment. The research instrument was a questionnaire, and the data were analyzed using multiple linear regression. The results showed that partially, family environment and lifestyle significantly influenced students' financial management, while financial literacy did not. This study concluded that simultaneously, financial literacy, family environment, and lifestyle significantly influenced students' financial management. However, partially, only the family environment and lifestyle had a significant effect, while financial literacy had no significant effect. Lifestyle was the most dominant factor influencing how students manage their finances. Simultaneously, all three variables significantly influenced financial management, with lifestyle being the dominant variable.